The Impact of High Government Debt on Economic Development in Somalia - Harun, Abdifatah Dahir (Multidisciplinary Journal of Horseed International University (MJHIU), 2024)
This study focuses on the impact of high government debt on economic development in Somalia. The specific objectives of the study encompass: to examine the impact of high government debt on Somalia's economic development, to explore the strategies that can be used to mitigate the negative impact of high government debt on economic development in Somalia and to evaluate the role of international financial institutions in managing high government in Somalia. This study employed descriptive research design and quantitative research method to investigate the impact of heavily-indebted on rebuilding economic development in Somalia. The study employed purposive sampling technique to select the participants of the study. The sample size of the study was 80 participants. To collect data from the respondents which they entail: Government officials, Economic analysts, representatives from financial institutions, Business owners and entrepreneurs, representatives from Non-governmental organizations (NGOs) and Academics (researchers and scholars). The study adopted close-ended questionnaire instrument data collected from the respondents of the study was entered, coded, sorted, organized and analyzed using Statistical Package Software Science (SPSS) version 28. The key findings of the study on the impacts of high government debt on Somalia's economic development entail: limited access to credit, increased debt servicing costs, inflation and currency depreciation, reduced investor confidence, limited fiscal space, vulnerability to external shocks and social unrest. The strategies the can be used to mitigate the negative impact of high government debt on economic development in Somalia include: promotion of financial literacy, strengthening regulatory framework, encouragement of diversification of the economy, Improving infrastructure and access to financial services, implementation of debt management strategies, fostering a conducive business environment and seeking external assistance and debt relief. And the role of international financial institutions in managing high government debt in Somalia entail: providing financial assistance, negotiating debt relief, offering technical expertise and supporting capacity-building. The study recommended that the Federal Government of Somalia should improve fiscal management and should work with international financial institutions and creditor countries to negotiate debt relief and restructuring agreements to reduce the burden of debt payments and boost economic development.